Detrital zircon U–Pb age and Hf isotopic composition from foreland sediments of the Assam Basin, NE India: Constraints on sediment provenance and tectonics of the Eastern Himalaya. (1st November 2015) - Vadlamani, Ravikant; Wu, Fu-Yuan; Ji, Wei-Qiang
Highlights: Eocene to Mio-Pliocene proposed Indian paleopositions track foreland sediment provenance. Provenance transition from Sylhet–Kopili Formations to the Barail Group. Late Eocene (∼40 Ma) earliest orogenic hinterland tectonic exhumation stage. Second major change in provenance within Miocene Surma Group. Related to time of main stage eastern Himalayan tectonic exhumation at ∼16 Ma. Abstract: Synorogenic Palaeogene–Neogene sediments of the Assam foreland basin, were derived by erosion of adjacent crustal and orogenic sources following the Greater India–Eurasia collision since ∼55 Ma. To constrain source sediment influx, and its relation to Himalayan tectonics, from pre- to post-collision time, detrital zircon U–Pb geochronology and their Hf isotopic compositions were carried out. The varying detrital zircon spectral patterns analyzed from the Paleogene Jaintia, Barail and Neogene Surma and Tipam Groups, with sediment petrography, track source sediment derived from cratonic India, Gangdese and eastern Transhimalayan batholiths and the eastern Himalaya. These sources are tested against Cenozoic paleopositions proposed for the northeastward motion of the Indian plate. Precollisional cratonic detritus to Middle to Late Eocene Sylhet Formation shifted to Tethyan Himalaya and arc sources of the Gangdese and eastern Transhimalayan batholiths to Late Eocene Kopili and Barail Formations, consistent with the proposed paleoposition proximal to the Indus-Yarlung suture. This Sylhet–Kopili Formation transition, within the Jaintia Group, reflects one of the earliest Himalayan hinterland exhumation stages during the Late Eocene. Major shift in provenance to Higher Himalayan Crystalline and arc detritus is recorded from the Surma Group, constraining Mid Miocene Himalayan tectonic exhumation from the eastern Himalaya. Late Miocene Tipam Group preserves sediment of Higher Himalayan Crystalline detritus, ophiolite and likely Lesser Himalayan rocks.